Comparative morphometric analysis of microglia in the spinal cord of SOD1G93A transgenic mouse model of amyotrophic lateral sclerosis. (4th April 2016) - Ohgomori, Tomohiro; Yamada, Jun; Takeuchi, Hideyuki; Kadomatsu, Kenji; Jinno, Shozo
Abstract: It has long been recognized that reactive microglia undergo a series of phenotypic changes accompanying morphological transformation. However, the morphological classification of microglia has not yet been achieved. To address this issue, here we morphometrically analysed three‐dimensionally reconstructed ionized calcium binding adaptor molecule 1‐immunoreactive (Iba1 + ) microglia in the ventral horn of the lumbar spinal cord of SOD1 G93A transgenic mice, a model of amyotrophic lateral sclerosis. The hierarchical cluster analysis revealed that microglia were objectively divided into four groups: type S (named after surveillant microglia) and types R1, R2 and R3 (named after reactive microglia). For the purpose of comparative morphometry, we also analysed two pharmacological disease models using wild‐type mice: 3, 3′‐iminodipropionitrile (IDPN)‐induced axonopathy and lipopolysaccharide (LPS)‐induced neuroinflammation. Type S microglia showed a typical ramified morphology of surveillant microglia, and were mostly observed in wild‐type controls. Type R1 microglia were seen at the early stage of disease in SOD1 G93A mice, and also frequently occurred in IDPN‐treated mice. They exhibited small cell bodies with shorter and simple processes. Type R2 microglia were morphologically similar to type R1 microglia, but only transiently occurred in the middle stage of disease in SOD1 G93A mice and in IDPN‐treated mice. Type R3 microglia exhibited a bushy shape, and were observed in the end stage of disease in SOD1 G93A mice and in LPS‐treated mice. These findings indicate that microglia of SOD1 G93A mice can be classified into four types, and also suggest that the phenotypic changes may be induced by the events related to axonopathy and neuroinflammation. Abstract : This study statistically examined the three‐dimensional morphometric data of microglia in the lumbar spinal cord of SOD1 G93A transgenic mice, a model of amyotrophic lateral sclerosis (ALS). The hierarchical cluster analysis indicates that microglia of SOD1 G93A mice can be objectively classified into four types. The comparative analysis using two pharmacological disease models of wild‐type mice, 3, 3′‐iminodipropionitrile (IDPN)‐induced axonopathy and lipopolysaccharide (LPS)‐induced neuroinflammation, suggests that the phenotypic changes of microglia may be induced by the events related to axonopathy and neuroinflammation.